Integrating Occupational Therapy Specific Assessments in Practice: Exploring Practitioner Experiences - Eric Asaba; Mio Nakamura; Akie Asaba; Anders Kottorp (Occupational Therapy International)
Background. Occupational therapists sometimes find it challenging to integrate client-centered and occupational therapy specific assessments in practice. The aim of this study was to explore the use of occupational therapy specific assessments such as the Assessment of Motor and Process Skills (AMPS) among occupational therapists in Sweden and Japan. Methods. Interviews and qualitative thematic analyses were utilized. Findings. Four themes are reported: (1) use it or lose it, (2) simply no space until after hours, (3) biggest barriers can be colleagues, and (4) being more specific: communication. Conclusion. In keeping with previous studies, occupational therapists often find it challenging to implement client-centered and occupation-based assessment tools into practice. However, more work is needed to understand how best practices can be incorporated into a changing occupational therapy daily practice.